Creativity and Autism Spectrum Conditions: a Hypothesis on Lewis Carroll (ENTHYMEMA, 2017)
The hypothesis formulated by Simon Baron-Cohen and his collaborators on the onset of autistic syndromes and their link with an excess of the so-called S brain is reflected in the work of Lewis Carroll, a formal logic and mathematics professor deeply inclined to visual and spatial descriptions, interested in affordances and systemic circuits, and devoid of empathic tendencies in creating his characters. In the future, this finding may serve as a test for predicting autism spectrum disorders and support the elaboration of narrative artefact for therapeutic purposes in relation to people with autism.